Development of a ginger harvester - Aris A. (Forest Research Institute Malaysia, 2015)
Ginger harvesting is a laborious, tedious and time consuming process which requires mechanization if the crop is to be cultivated in large areas. The objective of the study is to examine the performance of currently available machines for harvesting root crops. The available machines discussed were a root digger harvester, a single row root digger harvester and collector, and a double row root digger harvester and collector. The design concepts for a suitable ginger harvester were obtained based on the observations of these available machines, with focus on crop requirements and machine requirements. The ginger harvester will be based on a single row root digger harvester and collector with a targeted machine work rate of 0.2 ha/hour.